The anarchy of Black religion : a mystic song - Carter, J. Kameron, 1967- (Black outdoors., 2023)
"In The Anarchy of Black Religion, J. Kameron Carter argues that the modern re-invention of religion is inseparable from antiblackness, with whiteness and white supremacy acting as political theologies forming the modern world. Carter employs an understanding of religion as a structuring imagination of matter and culture, opening a way of thinking about racial histories, racial subjection, ontology, and the present as religious configurations. Given the extent to which religion exists within the colonial and capitalist cosmology of separability, Carter proposes "the black study of religion" as a practice that would work against the extractive, individualistic, and imperialist ideology of capitalism"--